KONSEP NUSYUZ DALAM KITAB FATHUL QARIB PERSPEKTIF MUBADALAH - Ihyak Ihyak (Journal of Innovation Research and Knowledge, 2022)
The understanding of nusyuzz which is only aimed at women can lead to an attitude of degrading women's dignity and encouraging domestic violence perpetrated by husbands against their wives. Domestic violence is any act against a person, especially a woman, related to physical, sexual, psychological misery or suffering or neglect of the household including threats to commit acts, coercion, or unlawful deprivation of liberty within the household. There are several phenomena that occur in society regarding violence experienced by women in a family. Women occupy the highest rank in cases of domestic violence. Nusyuz should be discussed from two directions, there is the wife's nusyuz to her husband (QS. An-Nisa ':34) and there is also the husband's nusyuz to the wife (Q.S An-Nisa': 128). In the perspective of muballah, nusyuz is the opposite of obedience. Both, nusyuz and obedient are reciprocal, because husband and wife are required to have a shared commitment to bring all goodness into the household (Jalbu al masholih) and avoid all evil from it (dar'u al mafasid). This research is pure literature, as the primary data source is the main data of the chapter nusyuz in the book of fathul qarib and QS an-Nisa 'verse 34, the method used in this research is descriptive analytical method with a gender perspective interpretation approach and philosophical theological. This study found that one concept of nusyuz in the book of Fathul Qorib only explains the nusyuz of a wife to her husband, there is no discussion of the nusyuz of a husband to his wife. The two concepts of nusyuz in mubadalah theory are all actions, behaviors carried out by one partner or both, which can diminish, weaken, break, and threaten the marriage bond, whatever its form. Thus, nusyuz can happen to anyone (husband or wife), and the solution can be from anyone (husband or wife). The three solutions to solve the problem of nusyuz are mauizatul hasanah, hajrun, shulh, ihsan, and taqwa.